2017
DOI: 10.1111/ijcp.13048
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid and cardiovascular risk: What genes can say

Abstract: Summmary Background Although the relationship of elevated serum uric acid levels and cardiovascular disease has been established in a great number of studies, the causal relevance of this finding remains ambiguous. An approach to evaluate the causal relevance of biomarkers is to exploit the natural randomised allocation of allelic variation in genes affecting their level, also known as Mendelian randomisation. Aim The aim of this paper is to review the current literature regarding serum uric acid levels and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
0
14
1
Order By: Relevance
“…Hyperuricemia is a risk factor for cardiovascular disease [2,4,67]; however, the findings of other studies are inconsistent [22], and in our study with data from the HWSC, we only observed an association among women. A meta-analysis reported a more pronounced increased risk for CHD mortality in women [67].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Hyperuricemia is a risk factor for cardiovascular disease [2,4,67]; however, the findings of other studies are inconsistent [22], and in our study with data from the HWSC, we only observed an association among women. A meta-analysis reported a more pronounced increased risk for CHD mortality in women [67].…”
Section: Discussioncontrasting
confidence: 75%
“…Hyperuricemia is necessary for the development of gout and is associated with chronic diseases like obesity, metabolic syndrome, insulin resistance, cardiovascular disease, hypertension, chronic kidney disease, and type 2 diabetes [1,2,3,4,5]. Globally, the prevalence of hyperuricemia is estimated to be 2.0–32.1%, and it is higher in men than in women [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The atherogenic effects of UA include induction of oxidative stress in cells, which reduces the bioavailability of nitric oxide - associated with the activity of platelets and endothelial cells and the differentiation of smooth muscle cells in the vascular system. On the other hand, UA can also have antioxidant properties that can prevent atherosclerosis and improve endothelial function [8].…”
Section: Introductionmentioning
confidence: 99%
“…The electroanalytical performance of the MN system was evaluated through examining the response to uric acid. The latter is a common biomarker in a range of clinical conditions, such as hypertension [22], kidney function [23], stroke [24] and cardiovascular disease [25,26]. It is little surprise therefore that there is an extensive literature base on its electrochemical detection and, with continuing advances in 2D carbon nanomaterials and other catalytic particles, continues to hold the interest of the diagnostics [27][28][29][30][31].…”
Section: Fabrication Methodologymentioning
confidence: 99%